Photoclick and Release: Co‐activation of Carbon Monoxide and a Fluorescent Self‐reporter, COS or Sulfonamide with Fast Kinetics. (23rd December 2022) - Liu, Miao; Wang, Yuhan; Yan, Zhicheng; Yang, Jiabin; Wu, Yongyou; Ding, Dawei; Ji, Xingyue
Abstract: Bioorthogonal prodrugs with both fast reaction kinetics and multiple outputs are highly desirable but are only found sporadically. Herein, we report a novel photoclick‐and‐release strategy for the co‐activation of carbon monoxide and a self‐reporter, carbonyl sulfide, or sulfonamide with fast reaction kinetics ( k : 1.4–22.6 M −1 s −1 ). Such a photoclick‐and‐release strategy was successfully applied in live cells to deliver carbon monoxide and a fluorescent self‐reporter, both of which exhibited pronounced antiproliferative activity against 4T1 cancer cells. It is conceivable that this photoclick‐and‐release strategy could find applications in other fields, in which a controlled bond cleavage is preferred. Abstract : Photoclick and release : A cyclopropenone scaffold was employed as a strained alkyne precursor for bioorthogonal prodrug design. Such a photoclick‐and‐release system not only resolved the stability issues of strained alkynes but also exhibited multiple outputs and relatively fast kinetics.